Identification of subspecies-divergent genetic loci responsible for mineral accumulation in rice grains - Huang, Zijian; Li, Sai; Lv, Zhaokun; Tian, Yan; Chen, Yibo; Zhu, Yuxing; Wang, Jiurong; Deng, Huabing; Sun, Liang; Tang, Wenbang (Frontiers in Genetics, 2023)
Rice (Oryza sativa L.) is a major staple food that provides not only dietary calories but also trace elements for the global inhabitants. The insufficiency of mineral nutrients and the potential accumulation of excessive toxic elements in grains pose risks to human health. The substantial natural variations in mineral accumulation in rice grains presents potentials for genetic improvements of rice via biofortifications of essential mineral nutrients and eliminations of toxic elements in grains. However, the genetic mechanisms underlying the natural variations in mineral accumulation have not been fully explored to date owing to unstable phenotypic variations, which are attributed to poor genetic performance and strong environmental effects. In this study, we first compared the genetic performance of different normalization approaches in determining the variations in grain-Cd, grain-Mn, and grain-Zn in different genetic populations of rice. Then through quantitative trait loci (QTLs) identification in two rice inter-ectype populations, three QTLs, including qCd7, qMn3, and qZn7, were identified and the QTLs were found to exhibit allelic differentiation in the different ecotypes. Our results were expected to broaden our understanding for mineral accumulation in rice and propose the potential functional alleles that can be explored for further genetic improvement of rice.